Sea otter heroes : the predators that saved an ecosystem - Newman, Patricia, 1958- (Millbrook Press, 2017)
Provides insight into the delicate balance of ecosystems and how the seagrass of the California coast inlet called Elkhorn Slough was saved by the activities of sea otters.